Reconfigurable optical‐radio wireless networks: Meeting the most stringent requirements of future communication systems. Issue 2 (31st January 2019) - Saud, Muhammad Saad; Ahmed, Iqrar; Kumpuniemi, Timo; Katz, Marcos
Abstract: In this paper, we propose a reconfigurable optical‐radio wireless network characterized by high flexibility and performance. The hybrid network can be dynamically configured, adapting itself to the changing requirements of users or operating environments, dynamics of the transmission medium, and availability of resources. First, the basic concept, system architecture, and key operating modes are introduced. Possible operating scenarios and their relationship to the operating modes are discussed. Then, a practical implementation of the hybrid network is introduced, describing the network components, architecture, modulation scheme, and implementation technologies. Implementation was carried out using mostly off‐the‐shelf components and universal software radio peripheral blocks. Particular attention has been put in implementing a fast handover mechanism between modes, an essential requirement for seamless network reconfiguration. Network performance is evaluated and different switching approaches are compared. The paper demonstrates practically the proposed concept based on dynamic system reconfiguration. For the implementation, a mode switching algorithm was developed making decisions based on the quality of the wireless channels. The system was tested with live video packets transmitted through the network. System performance was assessed through data throughput and packet loss measured for different modulation parameters. The proposed concept, essentially a software‐defined hybrid network, is flexible and makes efficient use of radio resources. Moreover, the network has the potential to achieve high performance. All these characteristics make reconfigurable optical‐radio networks an attractive candidate for fifth generation and beyond. Abstract : We implemented and tested a hybrid optical‐radio reconfigurable network. System is capable to switch between 5 operation modes. Live video packets transmitted through the network and observed that the system has potential to achieve a high performance. The characteristics of the system make the implemented reconfigurable optical‐radio network and attractive candidate for 5G and beyond.